The Influence of Online Review, Consumer Experience, and Service Quality on Homestay Customer Revisit Intention in Mandalika - Rohmiati, Rohmiati; Permadi, Lalu Adi (Raudhah Publisher, 2025)
This study aims to determine the influence of online reviews, consumer experience, and service quality on the revisit intention of homestay customers in Mandalika. The population used in this study is people who have stayed in homestays in Mandalika, with a sample of 100 respondents. The method used in this study is a quantitative approach of the causal associative type, which involves classical assumption tests and multiple linear regression. The results showed that the online review variable had a positive and significant effect on revisit intention in homestays in Mandalika, with a significance value of 0.000 < 0.05 and t count 4.243 > t table 1.984. Consumer experience also had a positive and significant effect on revisit intention in homestays in Mandalika, with a significance value of 0.000 < 0.05 and t count 3.777 > t table 1.984. In addition, service quality also showed a positive and significant influence on homestay intention revisit in Mandalika, with a significance value of 0.001 < 0.05 and t count 3.584 > 1.984.